عجز و تعجیزاور اس سے متعلقہ قواعد شر عیہ: ایک مطالعہA Study of ‘jz and Ta‘jīz and relevant Sharī‘ah Maxims (Al-Qamar, 2021)
This article studies ‘jz and Ta‘jīz and relevant Sharī‘ah Maxims. It maintains that easiness and concession is promoted by Islam in ‘Ibādāt (acts of worship), Mu‘āmalāt (Transactional dealings).This concept is endorsed by the Qur’ānic verses and Hadiths. Hardship and difficulties are alleviated by Sharī‘ah. There are many cases where alternatives are created. Many contracts are allowed for grant of easiness and for the removal of hardships from the people. Therefore this article will explain the Jurisprudential concept of ‘jz and Ta‘jīz عجز وتعجیز)) and the related maxims of Sharī‘ah as they are very important in the development of Fiqh. Many prepositions can be solved through these rules.
Keywords: jz, Ta‘jīz; Sharī‘ah Maxims